KINERJA PEMERINTAHAN DESA (Studi pada Kecamatan Sungai Raya Kabupaten Aceh Timur) - Zulyatami Lestari; Afrah Junita; Iqlima Azhar (Jurnal Mahasiswa Akuntansi Samudra, 2025)
This study aims to analyze the influence of village facilitators, regulations, and the use of the Village Financial System (SISKEUDES) application on the performance of village governance in Sungai Raya District, East Aceh Regency. This research employs a quantitative approach using multiple linear regression analysis. Data were collected through questionnaires distributed to 65 respondents, including village heads, secretaries, treasurers, village facilitators, and other village officials. The findings indicate that village facilitators, regulations, and the use of the SISKEUDES application significantly influence village governance performance, both partially and simultaneously. This suggests that optimizing the role of village facilitators, implementing effective regulations, and utilizing technology through the SISKEUDES application can enhance the efficiency and effectiveness of village governance. The study recommends improving the capacity of village facilitators, refining regulations, and providing intensive training on SISKEUDES usage for village officials to enhance transparency and accountability in village financial management. However, this research has several limitations, including regional coverage which is limited to Sungai Raya District, so the results cannot necessarily be generalized to other areas with different conditions. In addition, this research only focuses on three main variables, so other factors that have the potential to influence village government performance, such as human resource competency and community participation, have not been analyzed in depth. Therefore, it is hoped that further research can expand the regional coverage and add other relevant variables to obtain more comprehensive results.